2017
DOI: 10.2147/copd.s138006
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance therapy in COPD: time to phase out ICS and switch to the new LAMA/LABA inhalers?

Abstract: Long-term maintenance therapy for COPD is evolving rapidly. Dual bronchodilation with new long-acting muscarinic antagonist and long-acting beta-agonist (LAMA/LABA) fixed dose combination inhalers were introduced over the past 2 years. In clinical trials, these inhalers significantly improved lung function (trough forced expiratory volume in 1 second), patient-reported outcomes, and quality of life measures compared with placebo, their respective monocomponents, and tiotropium. The recorded adverse events of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…2,20 COPD is a complex disease with progressive destruction of functional lung tissue with few effective therapies. 1,21 These highlights the need for searching new molecular targets and active pathways involved in the progression of this disease. Here, we reported that activation of Wnt pathway by LiCl and AMPK by metformin protected against lung inflammatory responses and airspace enlargement, which is mediated by Nrf2 signal.…”
Section: Discussionmentioning
confidence: 99%
“…2,20 COPD is a complex disease with progressive destruction of functional lung tissue with few effective therapies. 1,21 These highlights the need for searching new molecular targets and active pathways involved in the progression of this disease. Here, we reported that activation of Wnt pathway by LiCl and AMPK by metformin protected against lung inflammatory responses and airspace enlargement, which is mediated by Nrf2 signal.…”
Section: Discussionmentioning
confidence: 99%
“…ICS is indicated for the treatment of patients with moderate-to-severe COPD and a history of exacerbations. Despite this, several studies have found that this does not reflect current clinical practice, and ICS is commonly prescribed in patients with less severe COPD [ 3 , 14 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 However, ICS withdrawal is not represented in the algorithm, because it was agreed by the panel that there is insufficient evidence to establish clear criteria as to when and how to discontinue ICS in patients with COPD. 24 …”
Section: Algorithm Of Pharmacologic Treatmentmentioning
confidence: 99%